2006
DOI: 10.1038/labinvest.3700423
|View full text |Cite
|
Sign up to set email alerts
|

The oligopeptide transporter hPepT1: gateway to the innate immune response

Abstract: Bacterial products that are normally present in the lumen of the colon, such as N-formylated peptides and muramyl-dipeptide, are important for inducing the development of mucosal inflammation. The intestinal dipeptide transporter, hPepT1, which is expressed in inflamed but not in noninflamed colonic epithelial cells, mediates the transport of these bacterial products into the cytosol of colonic epithelial cells. The small bacterial peptides subsequently induce an inflammatory response, including the induction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
2

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 110 publications
(159 reference statements)
1
45
1
Order By: Relevance
“…Based on our collective findings, we herein propose that the presence of leptin in inflamed colonic mucosa (25) could result to a local high concentration of leptin in contact with colonocytes. Our results suggest that the presence of high leptin concentrations result in increased intracellular cAMP in the colonic epithelial cells, triggering intracellular protein kinase signaling cascades, such as the second messenger system, leading to the subsequent phosphorylation/activation of CREB and Cdx2, which is followed by increased expression of hPepT1 and enhanced uptake of the small di-tri bacterial products that perpetuate intestinal inflammation (21). These findings provide important new insights into intestinal inflammation and may lead to new therapeutic modalities in the future.…”
Section: Discussionmentioning
confidence: 96%
“…Based on our collective findings, we herein propose that the presence of leptin in inflamed colonic mucosa (25) could result to a local high concentration of leptin in contact with colonocytes. Our results suggest that the presence of high leptin concentrations result in increased intracellular cAMP in the colonic epithelial cells, triggering intracellular protein kinase signaling cascades, such as the second messenger system, leading to the subsequent phosphorylation/activation of CREB and Cdx2, which is followed by increased expression of hPepT1 and enhanced uptake of the small di-tri bacterial products that perpetuate intestinal inflammation (21). These findings provide important new insights into intestinal inflammation and may lead to new therapeutic modalities in the future.…”
Section: Discussionmentioning
confidence: 96%
“…That might result in a greater capacity for peptide absorption during the first days of life in IUGR piglets [34] , thereby inducing a high load of antigens that may modulate immune system development [35] . In addition, the elevated expression of PEPT1, which potentially enhanced intestinal transport of bacterial peptides [36] , combined with the higher density of adherent bacteria and translocation, may result in a decrease in barrier function and subsequently may play a role in the IUGR-related modulation of the immune system via the NF-B pathway [37] . The change in the developmental pattern of intestinal IL-6 expression may be an illustration of these phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…15,38,39 In addition, we have previously demonstrated that PepT1 is also expressed in immune cells and may transport small proinflammatory peptides such as fMLP, thereby participating in the intestinal inflammatory responses. [20][21][22]48 Importantly, it has recently been shown that a PepT1 polymorphism is associated with IBD. Overall, our studies have revealed that PepT1 may be involved in the pathogenesis of IBD in humans.…”
Section: Discussionmentioning
confidence: 99%